The synergistic effect of body modification and surface coating for the moisture barrier of hydrophilic PU film - Yingfeng Xu; Yangyang Xiang; Luyao Bao; Guangan Zhang; Zhenjun Peng; Chunrong Tian; Bo Yu; Yanhua Liu; Feng Zhou (Journal of Materials Research and Technology, 2024)
Polyurethane (PU) films have established a distinctive position among various protective materials due to their outstanding chemical and physical properties. However, their limited moisture barrier performance hinders their broader applications. To solve this difficult problem, PU film is first modified by adding reactive fillers (MgO) and physical barrier fillers (Modified graphene oxide, M-GO), and then Si-DLC coating is deposited on the surface of the film by hollow cathode plasma immersion ion implantation (HCPIII) method at near room temperature. MgO can react with the water molecules diffused into the film, while the addition of M-GO extends the diffusion path of water molecules. It is revealed that the addition of 5% MgO and 0.5% M-GO, along with the deposition of a 2.56 μm Si-doped DLC coating, leads to a remarkable 14.67-fold reduction in the water vapor transmittance rate (WVTR). The result of molecular dynamics simulations shows that the reactive sheet filler captures the water molecules and reduces the WVTR. In addition, the combination method of PU body modification and surface coating is suitable for polyurethane foam (PUF) to reduce the WVTR as a double coating. It's amazing that the WVTR of PUF significantly reduces by 15.29 times after double-coating. The combination of body modification and surface coating provides an effective route for significantly improving the moisture barrier property of hydrophilic polymer film and polymer foam.